Risk indicators and risk predictors of dental caries in schoolchildren - Elaine Pereira da Silva Tagliaferro; Gláucia Maria Bovi Ambrosano; Marcelo de Castro Meneghim; Antonio Carlos Pereira (University of São Paulo, 2008)
The purpose of this study was to identify risk indicators of high caries level at baseline (HCLB) based on cross-sectional data and predictors of high caries increment (HCI) based on a 7-year-follow-up examination in 6-8-year-old schoolchildren. Two hundred and six schoolchildren were examined in 1997 and in 2004 by the same two calibrated dentists, in Piracicaba, Brazil. At baseline, dental caries, presence of sealants, fluorosis, and oral hygiene status were recorded. The children's parents completed a questionnaire concerning socioeconomic level, fluoride use, dental service utilization, dietary and oral hygiene habits. HCLB and HCI were defined considering the upper quartile of the total caries experience distribution (dmfs+DMFS) and caries increment distribution, respectively. Logistic regression models were adjusted estimating the Odds Ratio (OR), 95% confidence intervals and p-values. Having white spot lesions (OR=5.25) was found to be a risk indicator of HCLB. Schoolchildren with dental fluorosis (OR=0.17) or those who brushed the teeth more than two times a day (OR=0.37) presented less probability of HCLB. The predictors of HCI were: dmfs>0 (OR=2.68) and mothers' educational level up to 8 years of schooling (OR=2.87). Clinical and socioeconomic variables were found to be risk indicators and/or predictors of dental caries in schoolchildren.